544 VIII Steady Generalized Oseen Flow in Exterior Domains
The desired estimate for w
2
is then a consequence of (VIII.4.5 3), (VIII.4.60),
and (VIII.4.61). Concerning the stated properties of the pressure, we notice
that from (VIII.4 .47), (VIII.4.1) and from the Helmholtz–Weyl decomposition
theorem, Theorem III.1.2, it follows that
(∇φ(t), ∇χ) = (∇ · G(t), ∇χ) + (h(t), ∇χ) ,
for a.a. t ∈ (0, ∞), and all χ ∈ D
1,2
(R
3
).
(VIII.4.62)
We then choose in (VIII.4.62) the function χ as a solution to the Poisson
problem ∆χ = ψ, where ψ is arbitrary from C
∞
0
(R
3
). Recalling that from the
representation χ = E ∗ ψ, we have D
β
χ = O(|x|
1−|β|
), |β| ≥ 0, and using the
properties of φ and G, by (VIII.4.62) we easily obtain
(φ, ψ) = (G, ∇∇χ) −(h, ∇χ) . (VIII.4.63)
By Exercise II. 11.9, we have kD
2
χk
r
0
≤ ckψk
r
0
, for all r
0
∈ (1, ∞), and
k∇χk
3r
0
/(3−r
0
)
≤ ckD
2
χk
r
0
, for all r
0
∈ (1, 3). Thus, with the help of the
H¨older inequality, we obtain, on the one hand,
(G(t), ∇∇χ) ≤ c []G(t)[]
2,R
kψk
r
0
, for a.a. t ∈ (0, ∞), all r
0
∈ (1, ∞) .
(VIII.4.64)
On the other hand, since q > 3, we have q
0
< 3r
0
/(3 − r
0
) for all r
0
∈ (1, 3),
and consequently,
−(h(t), ∇χ) ≤ kh(t)k
q
k∇χk
q,B
ρ
≤ c
1
(ρ)kh(t)k
q
k∇χk
3r
0
/(3−r
0
)
≤ c
2
(ρ)kh(t)k
q
kD
2
χk
r
0
≤ c
3
(ρ)kh(t)k
q
kψk
r
0
,
for a .a. t ∈ (0, ∞), and all r
0
∈ (1, 3) .
(VIII.4.65)
Collecting (VIII.4.63)–(VIII.4.65) we conclude that
|(φ(t), ψ)| ≤ C
1
([]G(t)[]
2,R
+ kh(t)k
q
) kψk
r
0
, for a.a. t ∈ (0, ∞), all r
0
∈ (1, 3) ,
with C
1
depending o n r, q, and ρ. However, by Exercise II.2.12, this latter
inequality implies
ess sup
t≥0
kφ(t)k
r
≤ C
2
ess sup
t≥0
([]G(t)[]
2,R
+ kh(t)k
q
) ,
with C = C(r, q, ρ), and the proof of the first part of the theorem i s complete.
Assume next that G = 0 and h satisfies the further assumptions (VI II.4.49).
We then have w(x, t) ≡ w
2
(x, t), where w
2
satisfies (VIII.4.53), namely, re-
calling (VIII.4.52)
1
, we deduce
w
i
(x, t) =
Z
t
0
Z
B
ρ
Γ
ij
(x − y, τ ; R)h
j
(y, t − τ )dy dτ . (VIII.4.66)
We first consider the case R = 0. Differentiating both sides with respect to x,
and taking into account estimate (VIII.3.10) of Lemma VIII.3.3 , we obtain